Circulating corticosterone predicts near-term, while H/L ratio predicts long-term, survival in a long-lived seabird - Maness, Terri J.; Grace, Jacquelyn K.; Hirchak, Michael R.; Tompkins, Emily M.; Anderson, David J. (Frontiers in Ecology and Evolution, 2023)
Assessing stress in wild populations is important in many ecological and conservation contexts because the physiological responses of individuals to stressors can be used to identify at-risk populations and the ability to respond appropriately to stressors is related to individual quality and fitness. Yet, one of the great challenges in ecophysiology is linking physiological measures in wild animal populations with changes in individual fitness. Here, we examined two indices of stress, namely, circulating baseline corticosterone concentration ([Cort]) and the heterophil:lymphocyte (H/L) ratio, in a long-lived seabird, the Nazca booby (Sula granti) and their relationship with current individual state and subsequent survival and residual and lifetime reproductive success. [Cort] was related to sex, age, and current reproductive effort in in that males, older birds, and birds currently engaged in a breeding attempt birds had higher [Cort]. [Cort] was negatively associated with survival to the next breeding season. The H/L ratio was not associated with the current state of birds but predicted cohort-specific long-term survival. Lifespan and reproductive performance are correlated in Nazca boobies; therefore, our results suggest that the H/L ratio may be useful as an indicator of overall fitness, while [Cort] can be used to predict current or near-term fitness in this species. We further propose the H/L [or neutrophil/lymphocyte (N/L)] Ratio-Fitness Hypothesis, which posits that this ratio is repeatable within individuals and are negatively associated with fitness. This hypothesis needs to be tested in Nazca boobies and other species, and when supported by empirical evidence, then these ratios could be a powerful monitoring tool for assessing population health or identifying at-risk populations.